1974
DOI: 10.1007/bf00000017
|View full text |Cite
|
Sign up to set email alerts
|

Use of oleic acid derivatives to accelerate drying of thompson seedless grapes

Abstract: Pilot scale procedures were developed for the use of fatty acid ester emulsions to decrease the time to dry the Thompson seedless grapes to raisins. Both sun and mechanical drying were used in these experiments. Mechanically harvested grapes were dipped in a 1% or 2% fatty acid ester emulsion and dehydrated at drying times less than those required for the soda‐dipped raisins. Spraying grapes on the vine with a commercial ethyl ester mixture, which contained an emulsifier and added potassium carbonate, allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…This increases the drying rate. There have been some studies on the drying behavior of various fruits and vegetables such as grape (Doymaz & Pala, 2002a;Petrucci, Canata, Bolin, Fuller, & Stafford, 1974;Ponting & McBean, 1970;Saravacos et al, 1988), red pepper (Doymaz & Pala, 2002b) and corn (Doymaz & Pala, 2003;Suarez, Loncin, & Chirife, 1984). However, any work for the influence of ethyl oleate on the drying kinetics of mulberry has not been studied yet.…”
Section: Introductionmentioning
confidence: 96%
“…This increases the drying rate. There have been some studies on the drying behavior of various fruits and vegetables such as grape (Doymaz & Pala, 2002a;Petrucci, Canata, Bolin, Fuller, & Stafford, 1974;Ponting & McBean, 1970;Saravacos et al, 1988), red pepper (Doymaz & Pala, 2002b) and corn (Doymaz & Pala, 2003;Suarez, Loncin, & Chirife, 1984). However, any work for the influence of ethyl oleate on the drying kinetics of mulberry has not been studied yet.…”
Section: Introductionmentioning
confidence: 96%
“…Petrucci et al [2] found that the oleate emulsion reduced drying time of sundried raisins to 5-10 days. Ethyl or methyl oleate is mixed with water and potassium carbonate to form an emulsion that dissolves the wax cuticle.…”
Section: Introductionmentioning
confidence: 98%
“…Because, plums are covered naturally with a thin layer of (Bolin, Petrucci, & Fuller, 1975;Petrucci, Canata, Bolin, Fuller, & Stafford, 1974;Tulasidas, Raghavan, & Norris, 1996). Chemical pretreatment using a solution of ethyl oleate and sodium hydroxide, sodium carbonate were found efficient for grapes (Doymaz & Pala, 2002a;Ponting & McBean, 1970;Saravacos, Marousis, & Raouzeos, 1988), corn (Suarez, Loncin, & Chirife, 1984), apricot (Pala et al, 1996), and red pepper (Doymaz & Pala, 2002b).…”
Section: Introductionmentioning
confidence: 99%